Assessment, improvement, and comparison of different computational tools used for the simulation of heat transport in nanostructures. (March 2023) - Bea, EA; Mancardo Viotti, A; Carusela, MF; Monastra, AG; Soba, A
In this work we compare different implementations of two interatomic potential models, one the empirical Tersoff–Brenner and the other the semi-empirical tight-binding, to be used in the thermal transport study of silicon nanosystems. The calculations are based on molecular dynamics simulations. In the case of Tersoff–Brenner potential, two free software packages were used, while for tight-binding potential, an in-house code was developed. Both approaches require an enormous amount of computing effort, so the use of acceleration tools for adequate performance is crucial. We present a detailed study of each computational tool used: efficiency, advantages and disadvantages, and the results of application to the calculation of thermal conductance of structured silicon nanocrystals subjected to a temperature gradient.